2017
DOI: 10.1111/tid.12750
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis after kidney transplantation is associated with significantly impaired allograft function

Abstract: Post-transplantation TB was associated with a high incidence of AKI, and complete recovery of baseline renal function was not achieved after treatment. The severity of TB disease, AKI, and AR episodes that occurred after TB diagnosis are potential causes for this outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…[11,22] Owing to the difficulties in diagnosis and treatment, the mortality of active tuberculosis in renal transplant recipients is still 6% to 10% [4,15] with about 15% graft loss and a median GFR decrease of 10 mL/min during therapy. [23] In our case, the kidney transplant function even improved with therapy. This can partially be attributed to the reduction in cyclosporine doses but might also be because of renal involvement of tuberculosis, [24] which is supported by the sterile pyuria.…”
Section: Discussionmentioning
confidence: 58%
“…[11,22] Owing to the difficulties in diagnosis and treatment, the mortality of active tuberculosis in renal transplant recipients is still 6% to 10% [4,15] with about 15% graft loss and a median GFR decrease of 10 mL/min during therapy. [23] In our case, the kidney transplant function even improved with therapy. This can partially be attributed to the reduction in cyclosporine doses but might also be because of renal involvement of tuberculosis, [24] which is supported by the sterile pyuria.…”
Section: Discussionmentioning
confidence: 58%
“…Our study has certain strengths: (1) we included nationwide KT events in the recent period, (2) the study was performed in a nation with moderate TB prevalence, (3) we included a relatively large number of active TB cases, and (4) a comparison between the KT group and the matched dialysis or general population group was performed. [5][6][7]26 In the study, KT patients showed a significantly higher risk of active TB than the age-sex-matched general population group, even after adjusting the comorbidities. This is in accordance with the current guidelines suggesting additional screening for TB to be performed for potential KT recipients.…”
Section: Discussionmentioning
confidence: 75%
“…Costa et al showed that post-transplant tuberculosis in kidney transplant recipients was associated with a high incidence of acute kidney injury without recovery of baseline renal function after treatment. 5 Similarly, our patient was hospitalized due to an increase in creatinine and diagnosed with tuberculosis. The patient's creatinine level remained higher than baseline in the 3rd month of tuberculosis treatment.…”
Section: A Case Of Tuberculosis Mimicking Lung Cancer In a Kidney Transplant Recipientmentioning
confidence: 75%